A quasi-two-dimensional perovskite microcavity and its synthesis method and application
Through the synthesis method of quasi-two-dimensional perovskite microcavity, the precursor liquid spin coating and annealing technology is used to solve the problem of large size and wide wavelength in the existing technology, and the narrow line width and small wavelength are achieved Laser laser emission broadens application scenarios and improves preparation efficiency through the presence of organic ligands.
Patent Information
- Application Number
- CN202211220614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-10-08
AI Technical Summary
The CsPbBr3 perovskite microcavity prepared by conventional evaporation solution method in the prior art has a large crystal size, spontaneous radiation wavelength is concentrated at 535 nm and a wide half-maximum width, which limits its application range and is limited in preparation quantity.
The synthesis method of quasi-two-dimensional perovskite microcavity includes preparation of quasi-two-dimensional perovskite precursor, spin coating of precursor and sample annealing, by mixing butyl ammonium bromide, lead bromide and bromide in organic solvents Cesium, spin-coated on a quartz glass substrate and annealed at high temperatures, quasi-two-dimensional perovskite microcavity with narrow line widths and small wavelengths were prepared.
It has achieved low spontaneous radiation wavelength and low laser laser wavelength, broadened the laser application scenarios, and confirmed that the organic ligand is contained through EDS element analysis. A single preparation can obtain more microcavities and improve the preparation efficiency.
Smart Images

Figure CN115558982B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a chemical synthesis method and relates to a quasi-two-dimensional perovskite microcavity and a synthesis method and application thereof. Background Art
[0002] Micro laser sources play an extremely important role in optoelectronic information fields such as on-chip interaction, ultra-high resolution imaging and display, and high-density data storage. With the end face as the reflective cavity mirror and the material itself as the gain medium, semiconductor single crystal micro-nano structures such as nanowires and nanosheets naturally form a micro optically pumped laser. Metal halide perovskite materials have achieved great success in the field of solar cells due to their simple preparation process, high absorption coefficient, and long carrier transmission distance. As a semiconductor material, perovskite also has excellent luminescence properties, which makes it used in the production of luminescent microcavities.
[0003] CsPbBr is currently prepared by conventional evaporative solution method. 3 Perovskite microcavities have a large size, and the number of them grown on a substrate of equal area is limited. At the same time, the wavelength of their luminescence is generally concentrated at 535nm, and the half-peak width is often wide. The microcavity produced by a synthesis method of a quasi-two-dimensional perovskite microcavity has a smaller crystal size and a spontaneous radiation wavelength of less than 530nm. In terms of laser lasing performance, the quasi-two-dimensional perovskite microcavity has a smaller lasing wavelength, so it has a better performance than CsPbBr prepared by the conventional evaporation solution method. 3 Perovskite microcavities have a wider range of applications. Summary of the invention
[0004] In order to solve the deficiencies in the prior art, the present invention proposes a simple synthesis method that can prepare a large number of quasi-two-dimensional perovskite microcavities at one time.
[0005] The present invention proposes a method for synthesizing a quasi-two-dimensional perovskite microcavity, which achieves low spontaneous emission wavelength, low laser lasing wavelength and smaller crystal size. In addition, in the prepared quasi-two-dimensional perovskite microcavity (including but not limited to quasi-two-dimensional perovskite microwires or quasi-two-dimensional perovskite microdisks), EDS elemental analysis confirms that it does contain N element, that is, it contains organic ligands, which broadens the scenarios of its laser application and enables more microcavities to be obtained in a single preparation.
[0006] The present invention proposes a method for synthesizing a quasi-two-dimensional perovskite microcavity, and the synthesis steps include: preparing a quasi-two-dimensional perovskite precursor solution, spin coating the precursor solution, and annealing a sample; the quasi-two-dimensional perovskite precursor solution is intended to prepare a solution containing an organic ligand, lead bromide, and cesium bromide as a material for preparing a quasi-two-dimensional perovskite microcavity; the compounds are mixed in an organic solvent in a specific ratio, and stirred and heated at a specific temperature. The precursor solution spin coating is to spin coat the precursor solution on a quartz glass substrate through a homogenizer in the air. The precursor solution is spin coated on the quartz glass substrate placed in the homogenizer at a specific speed and time. The sample annealing is to anneal the spin-coated sample at a high temperature in the air to promote the growth of the quasi-two-dimensional perovskite microcavity. A high-temperature environment in the air is provided to the quasi-two-dimensional perovskite material attached to the quartz glass substrate. In this environment, the growth of the quasi-two-dimensional perovskite microcavity can be promoted.
[0007] In the quasi-two-dimensional perovskite precursor solution preparation step, butylammonium bromide, lead bromide and cesium bromide are mixed in proportion in an organic solvent, and stirred and heated at a temperature of 50-80°C (preferably, at 80°C, or also at 50, 60, or 70°C) to prepare a quasi-two-dimensional perovskite precursor solution.
[0008] The compounds include butylammonium bromide, lead bromide and cesium bromide. The molar ratio of butylammonium bromide, lead bromide and cesium bromide is in the range of 2-4:3-5:2-4; preferably, the ratio is 2:3:2.
[0009] The organic solvent includes N,N-dimethylformamide solvent, dimethyl sulfoxide, etc.; preferably, it is N,N-dimethylformamide solvent.
[0010] The quasi-two-dimensional perovskite precursor solution prepared by the method of the present invention is a (BA)2(Cs)n-1PbnBr3n+1 solution.
[0011] In a specific embodiment, in the step of preparing the quasi-two-dimensional perovskite precursor solution, butylammonium bromide, lead bromide and cesium bromide are added to N,N-dimethylformamide solvent in a molar ratio of 2:3:2 to prepare a quasi-two-dimensional perovskite precursor solution, i.e., 0.04 mol / L (BA) 2 (Cs) n-1 Pb n Br 3n+1 Solution.
[0012] In the present invention, in the precursor liquid spin coating step, a quartz glass substrate preheated at 50-100°C is placed on a coater, and after dripping the quasi-two-dimensional perovskite precursor liquid, spin coating is performed at a rotation speed of 400-600rpm / s for 4-6 seconds and at a rotation speed of 2000-3000rpm / s for 50-60 seconds.
[0013] Preferably, in a specific embodiment, a quartz glass substrate preheated at 100°C for 2 minutes is placed on a coater, and after 200uL of quasi-two-dimensional perovskite precursor solution is dripped on it, the rotation speed is maintained at 500rpm / s for 5 seconds and at 2500rpm / s for 55 seconds.
[0014] In the present invention, in the sample annealing step, the sample is placed on a heating table at 50-100°C and continuously heated to obtain a quasi-two-dimensional perovskite microcavity, that is, a quasi-two-dimensional perovskite microcavity with a narrow linewidth laser laser wavelength and a small wavelength of photoluminescence wavelength.
[0015] Preferably, when the sample is continuously heated on a heating platform at 100° C., the organic ligand butylammonium bromide and N,N-dimethylformamide solvent on its surface will evaporate, and the crystal will also grow in this process, thereby growing a quasi-two-dimensional perovskite microcavity.
[0016] In the synthesis method of the present invention, more quasi-two-dimensional perovskite microcavities can be obtained through a single preparation.
[0017] The quasi-two-dimensional perovskite microcavity of the present invention includes but is not limited to a quasi-two-dimensional perovskite microwire or a quasi-two-dimensional perovskite microdisk, etc.; preferably, it is a quasi-two-dimensional perovskite microwire.
[0018] In the synthesis method of the present invention, in the prepared quasi-two-dimensional perovskite microcavity (including but not limited to quasi-two-dimensional perovskite microwire or quasi-two-dimensional perovskite microdisk), EDS elemental analysis confirms that it does contain N element, that is, it contains organic ligands.
[0019] The present invention also provides a quasi-two-dimensional perovskite microcavity prepared by the above synthesis method. The quasi-two-dimensional perovskite microcavity has a laser lasing wavelength of 538nm and a size characteristic of 2um in width and 4um in length.
[0020] The present invention realizes a novel self-assembled quasi-two-dimensional perovskite microcavity, which realizes a narrow line width laser lasing wavelength and a smaller spontaneous emission wavelength of 525nm than that of the bromine lead cesium self-assembled perovskite microcavity. Its small wavelength and high intensity laser lasing wavelength contribute to the in-depth research of perovskite light-emitting microcavity.
[0021] The present invention also proposes the application of the quasi-two-dimensional perovskite microcavity, which is applied to the field of micro-nano lasers and can generate laser lasing with a narrow line width of 0.2 nm and a low wavelength of 538 nm.
[0022] The beneficial effects of the present invention include: it realizes low spontaneous emission wavelength and low laser lasing wavelength (e.g., 538nm), which broadens the scene of its laser application. Its smaller crystal size (e.g., 2um width, 4um length), and in the prepared quasi-two-dimensional perovskite microcavity (including but not limited to quasi-two-dimensional perovskite microwire or quasi-two-dimensional perovskite microdisk), after EDS elemental analysis, it is confirmed that it does contain N elements, that is, it contains organic ligands. And it enables more microcavities to be obtained in a single preparation, making the preparation more efficient, simpler and more convenient.
[0023] Compared with the existing perovskite microcavities, the quasi-two-dimensional perovskite microcavity obtained by the present invention is innovative in that it contains a quasi-two-dimensional perovskite component, realizes the characteristic of low-wavelength laser lasing of 538nm, and realizes that in the prepared quasi-two-dimensional perovskite microcavity (including but not limited to quasi-two-dimensional perovskite microwires or quasi-two-dimensional perovskite microdisks), EDS elemental analysis confirms that it does contain N element, that is, it contains organic ligands. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flowchart of the method for synthesizing a quasi-two-dimensional perovskite microcavity of the present invention;
[0025] Figure 2 The variable power laser lasing spectrum of the quasi-two-dimensional perovskite microcavity synthesized by the present invention;
[0026] Figure 3 This is a picture of the quasi-two-dimensional perovskite microcavity synthesized by the present invention taken with a scanning electron microscope;
[0027] Figure 4 The half-maximum width of the quasi-two-dimensional perovskite microwire laser emission is measured;
[0028] Figure 5 The EDS spectrum elements and element mapping spectra of the measured quasi-two-dimensional perovskite microwires;
[0029] Figure 6 The variable power laser lasing spectrum of the quasi-two-dimensional perovskite microdisk synthesized by the present invention;
[0030] Figure 7 The half-peak width of the main peak (short wavelength) of the quasi-two-dimensional perovskite microdisk laser emission is measured;
[0031] Figure 8 This is a picture of the quasi-two-dimensional perovskite microdisk synthesized by the present invention taken with a scanning electron microscope;
[0032] Fig. 9 These are the measured EDS spectrum elements and element mapping spectra of the quasi-two-dimensional perovskite microdisk. DETAILED DESCRIPTION
[0033] The invention is further described in detail in conjunction with the following specific embodiments and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention has no special restrictions. It should be pointed out that for ordinary technicians in the field, several variations and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0034] like Figure 1 As shown, the steps of the synthesis method of the quasi-two-dimensional perovskite microcavity of the present invention include: preparation of a quasi-two-dimensional perovskite precursor solution, spin coating of the precursor solution, and sample annealing.
[0035] Example 1, Quasi-two-dimensional (BA) 2 (Cs) n-1 Pb n Br 3n+1 The synthesis of perovskite microcavities is described.
[0036] The synthesis steps include the following:
[0037] (1) Add butylammonium bromide, lead bromide and cesium bromide in a ratio of 2:3:2 to 5 ml of N,N-dimethylformamide solvent to prepare 0.04 mol / L quasi-two-dimensional (BA) 2 (Cs) n-1 Pb n Br 3n+1 Perovskite solution.
[0038] (2) A quartz glass substrate preheated at 100°C for 2 minutes was placed on a coater. After 200uL of quasi-two-dimensional perovskite precursor solution was dripped on it, the coater was rotated at 500rpm / s for 5 seconds and at 2500rpm / s for 55 seconds.
[0039] (3) The sample is placed on a heating table at 100°C and heated continuously. The organic ligands and N,N-dimethylformamide solvent on its surface will evaporate, and the crystal will grow in this process, thus growing a quasi-two-dimensional perovskite microcavity.
[0040] The experimental results show that the present invention achieves low laser wavelength and narrow line width, such as Figure 2 , Figure 4 As shown, it has a laser lasing wavelength of 538 nm.
[0041] The present invention realizes a smaller crystal size of the microcavity, such as Figure 3 As shown, the microcavity size is 2um in width and 4um in length. The quasi-two-dimensional perovskite microwire prepared by the present invention is confirmed to contain nitrogen (N) element through EDS element analysis, that is, it contains organic ligand BA, such as Figure 5 shown.
[0042] Example 2, Quasi-two-dimensional (BA) 2 (Cs) n-1 Pb n Br 3n+1 The synthesis of perovskite microcavities is described.
[0043] The synthesis steps include the following:
[0044] (1) Add butylammonium bromide, lead bromide and cesium bromide in a ratio of 2:4:3 to 5 ml of N,N-dimethylformamide solvent to prepare 0.04 mol / L quasi-two-dimensional (BA) 2 (Cs) n-1 Pb n Br 3n+1 Perovskite solution.
[0045] (2) A quartz glass substrate preheated at 100°C for 2 minutes was placed on a coater. After 200uL of quasi-two-dimensional perovskite precursor solution was dripped on it, the coater was rotated at 500rpm / s for 5 seconds and at 2500rpm / s for 55 seconds.
[0046] (3) The sample is placed on a heating table at 100°C and heated continuously. The organic ligands and N,N-dimethylformamide solvent on its surface will evaporate, and the crystal will grow in this process, thus growing a quasi-two-dimensional perovskite microcavity.
[0047] The experimental results show that the present invention achieves low laser wavelength and narrow line width, such as Figure 6 , Figure 7 As shown, it has dual-mode laser lasing wavelengths of 538nm and 543nm.
[0048] The present invention realizes a smaller crystal size of the microcavity, such as Figure 8 As shown, the microcavity size is 2um×2um. The quasi-two-dimensional perovskite microwire prepared by the present invention is confirmed to contain nitrogen (N) element through EDS element analysis, that is, it contains organic ligand BA, such as Fig. 9 shown.
[0049] The protection content of the present invention is not limited to the above embodiments. The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of the substantive technical content of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A method for synthesizing a quasi-two-dimensional perovskite microcavity, characterized in that: The method comprises the following steps: preparing a quasi-two-dimensional perovskite precursor solution, spin coating the precursor solution, and annealing the sample; wherein, In the quasi-two-dimensional perovskite precursor solution preparation step, the compounds are mixed in an organic solvent in proportion, and stirred and heated at a temperature of 50-80° C. to prepare a quasi-two-dimensional perovskite precursor solution; In the step of preparing the quasi-two-dimensional perovskite precursor solution, the compounds are butylammonium bromide, lead bromide and cesium bromide; the molar ratio of butylammonium bromide, lead bromide and cesium bromide is 2-4:3-5:2-4; the prepared quasi-two-dimensional perovskite precursor solution is a (BA)2(Cs)n-1PbnBr3n+1 solution; In the precursor liquid spin coating step, the quasi-two-dimensional perovskite precursor liquid is dropped on a quartz glass substrate placed on a spin coater and spin coated; In the sample annealing step, the quasi-two-dimensional perovskite material attached to the quartz glass substrate is placed in a high-temperature environment in the air to obtain the quasi-two-dimensional perovskite microcavity; in the sample annealing step, continuous heating is performed on a heating table at 50-100° C.; the organic ligands and N,N-dimethylformamide solvent on the surface of the sample evaporate, accompanied by the growth of crystals, thereby growing a quasi-two-dimensional perovskite microcavity.
2. The method for synthesizing a quasi-two-dimensional perovskite microcavity according to claim 1, characterized in that: The molar ratio of the butylammonium bromide, lead bromide and cesium bromide is 2:3:
2.
3. The method for synthesizing a quasi-two-dimensional perovskite microcavity according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide solvent or dimethyl sulfoxide.
4. The method for synthesizing a quasi-two-dimensional perovskite microcavity according to claim 1, characterized in that: In the precursor liquid spin coating step, a quartz glass substrate preheated at 50-100°C is placed on a coater, and after the quasi-two-dimensional perovskite precursor liquid is dripped on it, spin coating is performed at a rotation speed of 400-600 rpm / s for 4-6 seconds and at a rotation speed of 2000-3000 rpm / s for 50-60 seconds.
5. The method for synthesizing a quasi-two-dimensional perovskite microcavity according to claim 4, characterized in that: In the precursor liquid spin coating step, a quartz glass substrate preheated at 100°C for 2 minutes was placed on a spin coater, and after 200uL of quasi-two-dimensional perovskite precursor liquid was dripped on it, the spin coater was rotated at 500rpm / s for 5 seconds and at 2500rpm / s for 55 seconds.
6. The method for synthesizing a quasi-two-dimensional perovskite microcavity according to claim 1, characterized in that: The quasi-two-dimensional perovskite microcavity includes a quasi-two-dimensional perovskite microwire or a quasi-two-dimensional perovskite microdisk; wherein, in the quasi-two-dimensional perovskite microwire or the quasi-two-dimensional perovskite microdisk, EDS elemental analysis confirms that it does contain N element, that is, contains organic ligands.
7. A quasi-two-dimensional perovskite microcavity synthesized by the synthesis method according to any one of claims 1 to 6, characterized in that: The quasi-two-dimensional perovskite microcavity has a laser lasing wavelength of 538 nm, a width of 2 um, and a length of 4 um.
8. The use of the quasi-two-dimensional perovskite microcavity as claimed in claim 7, characterized in that: The application is that the invention can be used in the field of micro-nano laser to generate laser lasing with a narrow line width of 0.2 nm and a low wavelength of 538 nm.
